Barth on Divine Simplicity and the Attributes of God: A Theological Agenda for Christian/Muslim Dialogue - Pickard, Stephen K. (International journal of public theology, 2021)
Abstract This article examines the theological concepts of divine simplicity and the attributes of God. The purpose of this inquiry is to explore the significance of these themes for Christian/Muslim dialogue. In this sense the article is an overture to a public theology undertaken through aspects of the doctrine of God foundational for Christians and Muslims. An introduction identifies the somewhat marginal significance of theological dialogue in Christian-Muslim encounter. In doing so it considers what contribution Karl Barth might have to make to Christian-Muslim reflections on the doctrine of God. The main focus of the article examines Barth’s treatment of divine simplicity and the attributes of God. In this respect the article highlights the importance of Barth’s ethical transposition of the doctrine of divine simplicity and its implications for inter-religious engagements in the world. The article argues for a public theology which takes more seriously the relationship between theory and practice in inter-religious dialogue.